Pamphlet beginning 'Le premier billet, qu'aye jamais receu le Sieur Rangeard, par l'ordre de la Compaignie de Messieurs les Medecins jurés de Bordeaux, est suivant, écrit et signé de la main de Mr Audat, ausse Medecin juré, le cinquiéme Novembre 1680.' - Rangeard, Jean (s.n, 1683)
Evidence of Rangeard's position as physician in Bordeaux. Pages 1-4: 'billets' (in French) received by Rangeard's demonstrating his membership of the Compaignie de Messieurs les Medecins jurés de Bordeaux and years of practice as a physician. Pages 5-7: convening of the Compaignie de Messieurs les Medecins jurés de Bordeaux (in Latin).